Chronostratigraphy and radiocarbon age inversion in the Holocene regressive barrier of Paraná, southern Brazil - Angulo, Rodolfo José; de Souza, Maria Cristina; Assine, Mario Luis [UNESP]; Pessenda, Luiz Carlos Ruiz; Disaró, Sibelle Trevisan (Elsevier, 2008)
Twenty-two 14C datings were performed at the central sector of the Paraná coast to define Holocene regressive barrier evolution. The barrier Pleistocene substratum was ascribed an age between 40 400 and 30 000 yr BP, but it can also represent the penultimate sea level highstand during marine isotope stage 5e. The Holocene barrier samples provided ages between 8542-8279 and 2987-2751 cal yr BP, and showed at least six age inversions that were related to age differences between in situ or low-distance transported shells or trunk fragments, and high-distance transported vegetal debris, wood fragments and organic matter samples. The regressive Holocene barrier age was 4402-4135 cal yr BP near the base, and 2987-2751 cal yr BP near the top. Most of the vegetal remains were transported by ebb tidal currents from the estuaries to the inner shelf below wave base level during the mid-Holocene highstand; they were transported onshore by storm waves and littoral currents during the sea level lowering after the sea level maximum, and were deposited mainly as middle shoreface swaley cross-stratification facies. © 2008.
Keywords: eastern Brazilian coast; Holocene regressive barrier; radiocarbon age inversion; transported vegetal debris dating; Chronostratigraphy; Holocene; Radiocarbon ages; chronostratigraphy; radiocarbon dating; sea level change; tidal current; Brazil; Parana; South America